Revitalisasi Tepung Tawar sebagai Perlindungan Budaya Lokal di Aceh Tamiang - Joko Hariadi; Muhammad Arif Fadhilah; Azrul Rizki; Indah Fajarini (Institut Seni Indonesia Denpasar, 2022)
This research aims to revitalize the tradition of Tepung Tawar as a form of strengthening and protecting local culture in Malay society in Aceh Tamiang Regency. This is a qualitative study that uses descriptive methodologies. Data is gathered using various methods, including interviews, documentation, and field observations. Data analysis is accomplished by presenting and condensing data from interviews and observations. The data is processed by describing the information gathered during the interview and observation procedure in the field. According to the findings of this study, 12 subdistricts in Aceh Tamiang continue to use Tepung Tawar in a variety of processes. 4 sub-districts conduct Tepung Tawar processions only on specific activities, namely Banda Mulia, Sekerak, Seruway, and Tamiang Hulu subdistricts. In the four sub-districts, the revitalization of the tradition of Tepung Tawar was carried out in coordination with the Chairman of MAA, indigenous elders, and community leaders. After conducting interviews and observations, it was discovered that the process of revitalizing the Tepung Tawar tradition is carried out in five ways, namely (1) procurement of competitions in the community about the tradition of Tepung Tawar, (2) training the village youth about the procession of Tepung Tawar, (3) strengthening the traditional institutions to pay attention to the procession of Tepung Tawar, and (4) strengthening the traditional institutions to pay attention to the procession of Tepung Tawar. The preservation and maintenance of local culture, Tepung Tawar, is necessary to prevent degradation soon.